Diabetes Meal Planning: Managing Your Carbohydrate Intake - Nancy Gal; Wendy J. Dahl (EDIS)
If you have diabetes, maintaining a consistent carbohydrate intake throughout the day is an effective meal-planning method to help maintain your target blood glucose levels. Foods that contain carbohydrates have the greatest effect on blood glucose levels compared to foods that contain primarily protein or fat. Carbohydrates in foods that contribute to blood glucose includes sugars and starches. The amount of carbohydrate you consume is based on your diabetes treatment goals and carbohydrate tolerance. This new 3-page publication of the UF/IFAS Food Science and Human Nutrition Department, written by Nancy J. Gal and Wendy J. Dahl, provides a strategy for planning your daily menu to manage your carbohydrate intake. https://edis.ifas.ufl.edu/fs324